Tinjauan Normatif Terhadap Praktik Dispensasi Kawin Anak Pasca Peningkatan Angka Pengajuan di Pengadilan Agama - Ubaidillah, Jefri (Laskar Karya, 2025)
Child marriage remains a serious issue in Indonesian family law, even though the minimum age of marriage has been raised to 19 years through Law No. 16/2019. The significant increase in marriage dispensation applications in religious courts indicates the existence of legal loopholes that allow the practice to continue. This study aims to examine the provisions of marriage dispensation in the Indonesian legal system, examine the legal loopholes, and analyse the impact on the protection of children's rights. The method used is normative juridical with a literature study approach. Primary legal materials consist of laws and the Compilation of Islamic Law, while secondary materials are books, journals and scientific articles. The analysis was conducted qualitatively. The results show that the phrase ‘very urgent reasons’ in Article 7 paragraph (2) has not been clearly formulated, leaving room for wide interpretation for judges. In addition, the implementation of PERMA No. 5/2019 has not been optimal in providing child protection. The novelty of this research lies in the normative and implementative evaluation of the regulation of marriage dispensation. This research recommends improving the rules and strengthening supervision so that marriage dispensation is no longer a loophole for legalising child marriage.